The development of executive functioning across the transition to first grade and its predictive value for academic achievement. (June 2017) - Vandenbroucke, Loren; Verschueren, Karine; Baeyens, Dieter
Abstract: Executive functions (EFs), used to guide goal-directed behavior, are essential for adequate classroom functioning. The current study aims to, (1) examine development and stability of three core EFs (working memory, inhibition, cognitive flexibility) across the transition to first grade; and (2) investigate the relationship of EFs with academic achievement, taking into account their multidimensionality and interconnections. EF tasks were administered at the end of kindergarten and first grade (n = 89) and standardized achievement tests at the end of first grade. Results indicate moderate to large growth and stability in working memory and cognitive flexibility and small improvements and stability in inhibition. Working memory predicted academic achievement, cognitive flexibility had a limited role and no additional contribution of inhibition was found. The current study suggests that the transitional period to first grade can be an important period to promote EF development, which in turn can support the prevention of later school problems. Highlights: Executive functions are essential for adequate functioning within the classroom. The transition to first grade is important for the development of executive functions. Working memory and cognitive flexibility show substantial growth and stability. Inhibition shows small improvements and limited stability. Working memory predicts academic achievement above inhibition and cognitive flexibility.